The Oncology Clinical Research Nurse Study Co-Ordinator: Past, Present, and Future - Elizabeth Ness (Elsevier, 2020)
Clinical research nursing is a specialty practice that has evolved over the past century. Clinical research nurses (CRNs) work directly (e.g., direct care provider and advance clinician) or indirectly (e.g., manager, educator, and study co-ordinator) to support clinic research. For more than 50 years, oncology nurses have contributed to the body of evidence describing and validating the responsibilities and importance of the nurse in clinical research, especially the study co-ordinator role. This article will focus on the CRN study co-ordinator role in oncology clinical trials highlighting the historical evolution of the role, the contributions of dedicated members of the Oncology Nursing Society, and the future landscape of clinical research nursing through the International Association of CRNs.